Racismo ambiental: "O que eu tenho a ver com isso?" diagnóstico do viés digital no caso Sol Nascente x Lago Sul através do Twitter - Azevedo, Fabíola Maria da Costa (Universidade Federal de São Carlos, 2024)
Environmental racism is one of the biggest concerns in the national territory today, and has been structured in a new conception that is already manifesting itself in the virtual environment. In this perspective, the theme of environmental racism carried out through the Web happens through network communication, where it is observed the way in which users connect, share information and construct meanings in this virtual environment that contributes to a more comprehensive view of contemporary communication. The present study aimed to analyze the way in which environmental racism is expressed in the virtual environment through Twitter in the case of Sol Nascente x Lago Sul through the post of Raphael Sebba. To do so, it was necessary to: a) identify which sets of posts (conversations) bring arguments related to the theme of environmental racism and which do not; and consequently, b) indicate which arguments and themes were found in the posts considered racist. A qualitative approach was used with content analysis on the social network Twitter. 43 conversations were analysed and 913 comments related to them. The collected data were submitted to data analysis using the MAXQDA software. The analysis of the data obtained found that of the 913 comments analyzed, 27.8% were considered racist – with an interconnection with the theme of environmental racism –. It is considered that the results obtained are useful for understanding the theme, which is still little understood by society, in addition to enabling the provocation for new research around the theme of environmental racism on the internet.
Environmental racism: diagnosis of digital bias in the Sol Nascente x Lago Sul case on Twitter
Keywords: Racismo ambiental; Ciência política; Comunicação; Environmental racism; Political science; Communication; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO